The Influence of Safety Observation on the 9 Building Blocks of Safety Model Canvas for a Dredging Company - Muhammad Bilal Teguh; Adithya Sudiarno (International Journal of Marine Engineering Innovation and Research, 2025)
The dredging industry's dynamic and high-risk operational environment makes its safety culture a critical factor in preventing occupational accidents. However, the complex interplay between different dimensions of safety culture in such a unique, project-based context is not yet fully understood. This research aims to develop and empirically test a structural model that explains the causal relationships among the nine core dimensions of the Safety Model Canvas and evaluates the influence of Safety Observation program within this framework. This study employed a quantitative approach using Partial Least Square Structural Equation Modeling (SEM-PLS). Data were collected from a major Indonesian dredging company through 50-item questionnaires administered to 95 employees and an analysis of 595 formal Safety Observation reports. A model with 12 hypothesized paths was tested to validate the theoretical framework. The analysis confirmed the model's validity, with 8 of the 12 hypotheses being statistically significant. The findings reveal that the Safety Observation program significantly enhances both Engagement & Involvement and Information & Communication. A robust operational pathway was identified where proactive leadership fosters worker engagement, which in turn builds responsibility. However, the model also uncovered a critical systemic weakness in the organizational learning process, indicating a failure to effectively translate safety information into enhanced worker competence. This study contributes a validated causal model of safety culture, offering significant theoretical and practical insights for safety management in project-based maritime industries.